2012
DOI: 10.1136/bjsports-2011-090520
|View full text |Cite
|
Sign up to set email alerts
|

Sport category is an important determinant of cardiac adaptation: an MRI study

Abstract: This study demonstrates a balanced cardiac adaptation with preserved ratios of LV/right ventricular volume (in all sport categories) and LV volume/wall mass (in LD-HS and HD-LS sports). Sport category has a strong impact on cardiac adaptation. HD-HS sports show the largest changes, whereas LD-HS sports show dimensions similar to non-athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 37 publications
2
47
0
3
Order By: Relevance
“…Recently, RV adaptations to exercise training have gained increased research interest. While previous studies concerning the effects of training on the RV have reported balanced hypertrophy with the LV (21,(35)(36)(37), other studies have reported RV dysfunction following intense endurance exercise (3,9,10,25,26,40). A recent meta-analysis further confirmed that prolonged intense exercise leads to reduction of RV function, while LV function remains unaffected (6), underlining the need for further studies specifically on RV adaptations.…”
mentioning
confidence: 63%
“…Recently, RV adaptations to exercise training have gained increased research interest. While previous studies concerning the effects of training on the RV have reported balanced hypertrophy with the LV (21,(35)(36)(37), other studies have reported RV dysfunction following intense endurance exercise (3,9,10,25,26,40). A recent meta-analysis further confirmed that prolonged intense exercise leads to reduction of RV function, while LV function remains unaffected (6), underlining the need for further studies specifically on RV adaptations.…”
mentioning
confidence: 63%
“…31 Além disso, esse fenômeno também pode estar relacionado à influência do meio da nutrição esportiva, devido ao fato de os indivíduos acreditarem que esses produtos lhe darão maior vantagem estética quando, na verdade, podem torna-se prejudiciais à saúde, com o aumento do risco de desenvolvimento de patologia cardiovascular. De fato, pesquisas recentes demonstram que o uso abusivo de EAA em atletas de força pode levar até a morte devido a alterações como: disfunção ventricular 50 , fibrose e morte de miócitos no ventrículo esquerdo 51 , desintegração das fibras musculares cardíacas e perda de discos intercalares e bandas-Z. 52 Em relação às substâncias relatadas pelos usuários de EAA, os estudos demonstram que a Decanoato de Nandrolona 53, 54 corresponde a 76% de utilização pelos adeptos de musculação, seguida pela Testosterona 53, 54 (71%) e Estanozolol 53, 54 (77%) 8 , ainda podendo permutar a ordem de preferência pelos usuários.…”
Section: Prevalência Dos Esteroides Anabólicos Androgênicos No Brasilunclassified
“…This included a comparison of LV diameter with established reference values and assessment of abnormal ECG parameters 6. ECGs were assessed by experienced cardiologists, using the Sokolow-Lyon criteria for the presence of LVH in all HCM participants, in all healthy athletes with borderline LVH and in a large subset of healthy athletes and non-athletes who were also evaluated in an earlier study 13 14…”
Section: Methodsmentioning
confidence: 99%